Repotenciación y automatización de una máquina rebobinadora marca KAMPF ubicada en las instalaciones de la empresa PREPACKING S.C.C.A - Hernández Rosero, Carlos Alberto (2017)
The KAMPF brand rewinder machine that is in the company Prepaking S.C.C.A, was acquired in 2006 is a second hand machine that at the moment is disabled, due to its mechanical and electronic elements have deteriorated and require a preventive maintenance And corrective. Prepacking S.C.C.A, is a company dedicated to the manufacture of plastic rolls for automatic food packaging, the demand generated by its customers is in continuous growth and therefore requires the rewinder of KAMPF brand to develop an automatic rewinding system of Plastic, Using a Siemens PLC because the company has its inventory with this brand of controler. In the elaboration of this project, was realized the characterization of the whole machine, preventive and corrective maintenance of mechanical and electronic parts, the design of an automatic plastic rewind system. AC motors control for plastic tension and operating speed, the material is mounted on the rollers belonging to the KAMPF machine. For the instrumentation of the project uses a PLC and a frequency inverter to control the operation of AC motors, also an account with an HMI screen where the user enters the values of speed and tension depending on the material of the plastic a rewind. Obtain the results obtained by automating the machine by testing the material given by the company.